2009
DOI: 10.1083/jcb.200909063
|View full text |Cite
|
Sign up to set email alerts
|

PtdIns4P recognition by Vps74/GOLPH3 links PtdIns 4-kinase signaling to retrograde Golgi trafficking

Abstract: Retention of Golgi-resident integral membrane proteins depends on the supply of PI(4)P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
186
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(191 citation statements)
references
References 59 publications
5
186
0
Order By: Relevance
“…The cDNA of HA-tagged GOLPH3 (a generous gift from Dr. Lynda Chin, Institute for Applied Cancer Science, University of Texas MD Anderson Cancer Center) (21) and HA-tagged, shRNA resistance GOLPH3 were cloned by standard PCR protocols, into pENTR/D-TOPO (Invitrogen). The overlap extension PCRs were used to construct GOLPH3 mutants, which lacks a tetramer formation (⌬190 -201) (28) or the binding to PI4P (R171A/R174A and W81A/R90A) (29). The cDNAs of human ␣2,3-sialyltransferase-IV (ST3GAL4), ST6GAL1, and ␤1,4-galactosyltransferase I (␤4GALT1) (kindly provided by Dr. H. Narimatsu from National Institute of Advanced Industrial Science and Technology, Japan) were inserted into pENTR 1A tagged with 3ϫFLAG at the C terminus using the in-fusion method (Takara Bio).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cDNA of HA-tagged GOLPH3 (a generous gift from Dr. Lynda Chin, Institute for Applied Cancer Science, University of Texas MD Anderson Cancer Center) (21) and HA-tagged, shRNA resistance GOLPH3 were cloned by standard PCR protocols, into pENTR/D-TOPO (Invitrogen). The overlap extension PCRs were used to construct GOLPH3 mutants, which lacks a tetramer formation (⌬190 -201) (28) or the binding to PI4P (R171A/R174A and W81A/R90A) (29). The cDNAs of human ␣2,3-sialyltransferase-IV (ST3GAL4), ST6GAL1, and ␤1,4-galactosyltransferase I (␤4GALT1) (kindly provided by Dr. H. Narimatsu from National Institute of Advanced Industrial Science and Technology, Japan) were inserted into pENTR 1A tagged with 3ϫFLAG at the C terminus using the in-fusion method (Takara Bio).…”
Section: Methodsmentioning
confidence: 99%
“…GOLPH3 Was Specifically Associated with SialyltransferasesIn yeast cells, Vps74p, which is a counterpart of GOLPH3, was associated with mannosyltransferase enzyme (26), coatomer (45), phosphatidylinositol 4-phosphate (PI4P) (29), and regulated N-glycan synthesis. Very recently, GCNT1 enzyme was reported to be one of the putative binding partners for GOLPH3 to retain its Golgi localization (27).…”
Section: Forced Expression Of St6gal1 Rescued Cell Migration and Akt mentioning
confidence: 99%
See 2 more Smart Citations
“…GOLPH3 was initially detected as a phosphorylated protein localized to the Golgi apparatus (Dippold et al, 2009;Scott and Chin 2010). Recently, the cell biological, biochemical and functional analyses have shown that GOLPH3 can increase cell transformation and tumor growth by enhancing the activity of mTORC (Dippold et al, 2009;Wood et al, 2009;Scott and Chin 2010;Graham and Burd, 2011). Moreover, the preliminary First Affiliated Hospital, Henan University of Science and Technology,Luoyang,Henan,China *For correspondence: wangqiang_henan@163.com Qiang Wang* , Xian Wang, Can-Bin Zhang researches shown that GOLPH3 is relative with poor prognosis of some tumors, including gastric cancer (Hu et al, 2013) and esophageal squamous cell carcinoma (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%